2006
DOI: 10.1021/es061601e
|View full text |Cite
|
Sign up to set email alerts
|

Tropospheric Phosphine and Its Sources in Coastal Antarctica

Abstract: Earlier reports show very low concentrations of phosphine in remote air of the lower troposphere of nonpolar regions, in the low ng m(-3) range during the night and in the pg m(-3) range during daylight around noon. In this study, abnormally and unexpectedly high phosphine concentrations (30.0-407.8 ng m(-3), 11 locations) were found in polar air samples collected on Millor Peninsula, eastern Antarctica and Fildes Peninsula, western Antarctica. The maximum concentration was measured in the atmosphere of pengui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 31 publications
3
40
0
1
Order By: Relevance
“…Therefore the gas samples collected at the normal sites were insignificantly affected by human activities at Zhongshan Station, and the measured G values of N 2 O in the atmospheric samples can reflect its natural isotopic abundance. On the other hand, we have also observed the high N 2 O emissions from Wolong Beach Marsh, empire penguin colony and other related areas on this peninsula [25,29,30,38,39] . The N 2 O isotopic fractionation occurs during the microbial nitrification and denitrification in the soils or sediments, which brings about the isotopically light N 2 O ( 15 N and 18 O-depleted) into local atmosphere.…”
Section: The G Values Of Atmospheric N 2 O On Millor Peninsulasupporting
confidence: 51%
See 1 more Smart Citation
“…Therefore the gas samples collected at the normal sites were insignificantly affected by human activities at Zhongshan Station, and the measured G values of N 2 O in the atmospheric samples can reflect its natural isotopic abundance. On the other hand, we have also observed the high N 2 O emissions from Wolong Beach Marsh, empire penguin colony and other related areas on this peninsula [25,29,30,38,39] . The N 2 O isotopic fractionation occurs during the microbial nitrification and denitrification in the soils or sediments, which brings about the isotopically light N 2 O ( 15 N and 18 O-depleted) into local atmosphere.…”
Section: The G Values Of Atmospheric N 2 O On Millor Peninsulasupporting
confidence: 51%
“…(a) The sampling sites above the oceanic surface from Shanghai to 60°S; (b) the sampling sites from 60°S to Zhongshan Station and the location of Millor Peninsula; (c) the sampling sites for the gas samples near the surface on Millor Peninsula: 1, Empire penguin colony; 2, Wolong Beach Marsh; 3, the hilltop behind Russian Progress Station; 4, the normal observation site on the hilltop behind Zhongshan Station; 5, Tuanjie Lake; 6, Mochou Lake; 7, Nella Bay; 8, Luojiashan Icecap. sparse, the biological and chemical weathering processes are very weak and no true soil develops in this area due to severe climatic conditions and exposure to the bedrock [25,26] . The normal observation site (the site 4) for atmospheric N 2 O was set up on a hilltop (about 30 m asl) approximately 300 m to the southwest of Zhongshan Station (Figure 1(c)).…”
Section: Study Areamentioning
confidence: 99%
“…Our results were similar to those of previous studies (Han et al 2011b). MBP was positively correlated with Fe and negatively corrected with Mn in the biosphere (Zhu et al 2006), but we observed that neither Fe nor Mn 2+ was significantly correlated with MBP, which was attributed to different PH 3 production mechanisms in different ecosystems. Soil temperature was significantly negatively correlated with MBP levels, but in a relatively high and narrow range (33.03-22.10°C) suggesting that the decreased elimination rate of phosphine was more important than the increased production rate (Han et al 2011a;Niu et al 2013b).…”
Section: Discussionsupporting
confidence: 92%
“…The strong relationship between d 15 N and [P] values is consistent with this suggestion. However, bird colonies were not evident at lichen collection sites[1 km from the rookery and the link between d 15 N and [P] could equally be due to long distance dispersal of penguin-derived P in the form of P-laden aerosol and/or phosphine (Zhu et al 2006), and/or up-regulation of PME activity in N-enriched lichens. South polar skuas nest in the vicinity of the penguin rookery and snow petrels have been occasionally sighted; note that Cocks et al (1998) showed that d…”
mentioning
confidence: 99%